URANIUM MINES IN BULGARIA - ANALYSIS OF THE STATE 30 YEARS AFTER THEIR CLOSURE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Uranium mining in Bulgaria dates back to 1939 and was made a historical aspect of uranium mining in Bulgaria until its liquidation in 1992. The measures taken under Decree No. 74 / 27.03.1998 to liquidate the consequences of mining and processing are described of uranium and the omissions to be made. eliminated in this regard. Until the end of uranium mining in 1992, the annual production of uranium was 660-680 t, of which 430 t was obtained by geotechnical method - drilling with sand-type uranium drilling. They are poor in uranium (below 0.05%), but with several times cheaper yields (average $40/kg for 1970-1990). The problems related to the reclamation of lands around uranium deposits and enterprises are shown. The condition of the terrain around the mines and the results of the samples from 2000 and 2010 have been analysed and recommendations for improving the condition and subsequent investigation of the condition of the adjacent terrain have been identified.